Pembrolizumab‐induced acquired perforating dermatosis - Yaron Gu; Dinuke deSilva; Christopher J. A. Henderson; Deshan F. Sebaratnam (JEADV Clinical Practice, 2024)
Abstract Immune checkpoint inhibitors such as the programmed cell death‐1 (PD‐1) inhibitors, pembrolizumab and nivolumab, are frontline treatments for several types of solid‐organ malignancies. However, cutaneous adverse effects with PD‐1 inhibitor therapy are common and include lichenoid reactions, eczema, vitiligo and bullous dermatoses. Perforating dermatosis is a rare condition characterised by the extrusion of degenerate materials from the upper dermis through the epidermis and has rarely been reported in association with PD‐1 inhibitor therapy. Herein, we report the first case to our knowledge of acquired perforating dermatosis following treatment with pembrolizumab.